Association of dietary intake of milk and dairy products with blood concentrations of insulin-like growth factor 1 (IGF-1) in Bavarian adults - Romo Ventura, Eugenia; Konigorski, Stefan; Rohrmann, Sabine; Schneider, Harald; Stalla, Guenter K.; Pischon, Tobias; Linseisen, Jakob; Nimptsch, Katharina (European journal of nutrition, 2020)
Purpose Circulating IGF-1 concentrations have been associated with higher cancer risk, particularly prostate, breast and colorectal cancer. There is evidence from observational and intervention studies that milk and dairy products intake is associated with higher IGF-1 concentrations, but results were not always consistent. The purpose of this study was to examine the relationship between dairy intake and circulating IGF-1 concentrations in participants of the Second Bavarian Food Consumption Survey, thereby providing data for a German population for the first time. Methods In this cross-sectional study of 526 men and women aged 18–80 years, in contrast to most previous investigations, dietary intake was assessed with a more detailed instrument than food frequency questionnaires (FFQs), i.e., by three 24-h dietary recalls conducted on random days close in time to the blood collection. Circulating IGF-1 concentrations were measured in blood samples. Multivariable linear regression models were used to examine the association of dairy intake with IGF-1 concentrations. Results Each 400 g increment in daily dairy intake was associated with 16.8 µg/L (95% CI 6.9, 26.7) higher IGF-1 concentrations. Each 200 g increment in milk per day was associated with 10.0 µg/L (95% CI 4.2, 15.8) higher IGF-1. In contrast, we observed no association between cheese or yogurt intake and IGF-1 concentrations. Conclusions Our findings are in line with most previous investigations and support the hypothesis that dairy and milk intake are associated with higher IGF-1 concentrations.